Maternal kidney function during pregnancy: systematic review and meta‐analysis. (6th August 2019) - Lopes van Balen, V. A.; van Gansewinkel, T. A. G.; de Haas, S.; Spaan, J. J.; Ghossein‐Doha, C.; van Kuijk, S. M. J.; van Drongelen, J.; Cornelis, T.; Spaanderman, M. E. A.
ABSTRACT: Objectives: To review systematically current literature on kidney function changes during pregnancy, in order to estimate the extent of adaptation over the course of both healthy physiological and complicated singleton pregnancies, and to determine healthy pregnancy reference values. Methods: PubMed (NCBI) and EMBASE (Ovid) electronic databases were searched, from inception to July 2017, for studies on kidney function during uncomplicated and complicated pregnancies. Included studies were required to report a non‐pregnant reference value of kidney function (either in a non‐pregnant control group or as a prepregnancy or postpartum measurement) and a pregnancy measurement at a predetermined and reported gestational age. Kidney function measures assessed were glomerular filtration rate (GFR) measured by inulin clearance, GFR measured by creatinine clearance and serum creatinine level. Pooled mean differences between pregnancy measurements and reference values were calculated for predefined intervals of gestational age in uncomplicated and complicated pregnancies using a random‐effects model described by DerSimonian and Laird. Results: Twenty‐nine studies met the inclusion criteria and were included in the analysis. As early as the first trimester, GFR was increased by up to 40–50% in physiological pregnancy when compared with non‐pregnant values. Inulin clearance in uncomplicated pregnancy was highest at 36–41 weeks, with a 55.6% (53.7; 95% CI, 44.7–62.6 mL/min) increase when compared with non‐pregnant values, and creatinine clearance was highest at 15–21 weeks' gestation, with a 37.6% (36.6; 95% CI, 26.2–46.9 mL/min) increase. Decrease in serum creatinine level in uncomplicated pregnancy was most prominent at 15–21 weeks, with a 23.2% (−0.19; 95% CI, −0.23 to −0.15 mg/dL) decrease when compared with non‐pregnant values. Eight studies reported on pregnancies complicated by a hypertensive disorder. Meta‐regression analysis showed a significant difference in all kidney function parameters when comparing uncomplicated and hypertensive complicated pregnancies. Conclusions: In healthy pregnancy, GFR is increased as early as the first trimester, as compared with non‐pregnant values, and the kidneys continue to function at a higher rate throughout gestation. In contrast, kidney function is decreased in hypertensive pregnancy. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.